Предмет: Математика, автор: janatenison

(3/2x-y)-(2/2x+y)-(1/2x-5y):y²/4x²-y²
помогите пожалуйста

Ответы

Автор ответа: Аноним
0
(3(2x+y)-2(2x-y))/(4x²-y²) * (4x²-y²)/(2x-5y)=(6x+3y-4x+2y)/(2x-5y)=(2x+5y)/(2x-5y)
Автор ответа: tanya2512
0
( frac{3}{2x-y} - frac{2}{2x+y} - frac{1}{2x-5y} )* frac{4 x^{2} - y^{2}}{ y^{2}} =
 frac{(6x+3y)(2x-5y)-(4x-2y)(2x-5y)-(2x-y)(2x+y)}{ y^{2} (2x-5y)} =
frac{(2x-5y)(6x+3y-4x+2y)-(2x-y)(2x+y)}{ y^{2} (2x-5y)} =frac{(2x-5y)(2x+5y)-(2x-y)(2x+y)}{ y^{2} (2x-5y)} =
frac{(4 x^{2} -25 y^{2}-4 x^{2} + y^{2})}{ y^{2} (2x-5y)} = frac{-24}{2x-5y}

Похожие вопросы
Предмет: Алгебра, автор: Dikvlnk
Предмет: Математика, автор: darishkkka